Systemic oxidative stress associates with delirium in a geriatric population with hip fracture - Monika Trzpis; Maria Zernova; Karin M. Vermeulen; Marian L.C. Bulthuis; Marjan Reinders-Luinge; Harry van Goor; Barbara C. van Munster; Arno R. Bourgonje (Experimental Gerontology)
Background: Oxidative stress ensues in patients undergoing surgery for hip fracture and has been implicated in the pathophysiology of delirium. Circulating free thiols (R-SH, sulfhydryl groups) serve as biomarker of systemic oxidative stress since they are rapidly oxidized by reactive species, acting as potent antioxidants. We aimed to investigate the relationship between delirium and systemic oxidative stress in older patients hospitalized with hip fracture. Methods: Patients aged 65 years or more, acutely admitted due to hip fracture, were included between 2005 and 2008. Delirium was diagnosed according to the DSM-IV criteria for delirium. Free thiols were determined in plasma samples that had been collected longitudinally during hospitalization for previous clinical trial, using colorimetric detection. Albumin-adjusted plasma free thiol concentrations were both cross-sectionally and longitudinally evaluated in relation to delirium. Results: In total 813 plasma samples from 336 patients were analysed. Delirium was experienced by 110 (33 %) patients. Mean albumin-adjusted free thiols of patients who experienced delirium (7.3 ± SD 1.4 μM/g) was lower than that of non-delirious patients (7.5 ± SD 1.3 μM/g) (P = 0.050). Multivariable logistic regression analysis, adjusted for age, preexisting cognitive impairment, institutionalization, time to surgery, and complications, indicated that delirium was significantly inversely associated with albumin-adjusted free thiol concentrations (OR = 0.8, 95%CI 0.75–0.96). The significant association between delirium and albumin-adjusted free thiols tested in all the samples was also shown by linear mixed model analysis after adjusting for confounders (β = −0.292; 95%CI 0.04–0.55). Conclusions: Reduced concentrations of free thiols, reflecting systemic oxidative stress, are associated with delirium onset among patients with hip fracture.